Advancing the democratic participatory experiences of young people: the participatory budgets - Abellán-López, María Ángeles; Pardo-Beneyto, Gonzalo (Cadernos Metrópole, 2025)
This study examines the implementation of participatory budgets for children and adolescents (Childhood) in municipalities within the Valencian Community, Spain. These initiatives engage young people in public resource allocation decisions, promoting civic education, and democratic socialization. This study employs qualitative methods, including surveys and content analysis, to explore these participatory dynamics. This surveys include open questions. This research reveals a prevailing adult-centric bias and a tendency to prioritize the technical aspects of democratic education. These preliminary findings highlight significant obstacles, such as adult centrism and tokenism, which undermine the genuine influence of youth on decision-making processes. The study concludes that a more inclusive and educational approach is necessary to fully realize the potential of these participatory experiences. DOI: https://doi.org/10.1590/2236-9996.2025-6368054-en https://doi.org/10.1590/2236-9996.2025-6368054-es